Metacognitive Feelings, self-ascriptions and mental actions (2014)
ABSTRACT: The main aim of this paper is to clarify the relation between epistemic feelings, mental action, and self-ascription. Acting mentally and/or thinking about one’s mental states are two possible outcomes of epistemic or metacognitive feelings. Our mental actions are often guided by our E-feelings, such as when we check what we just saw based on a feeling of visual uncertainty; but thought about our own perceptual states and capacities can also be triggered by the same E-feelings. The first section of the paper presents Dokic’s argument for the insufficiency of the “ascent routine” to account for non-transparent cases of self-ascription, as well as his account of E-feelings. The second section then presents a two-level model of metacognition that builds on Dokic’s account and my own view of the issue. The two-level model links E-feelings to a mindreading capacity in order to account for non-transparent self-ascriptions. Finally, the third section develops a deeper characterization of the relation among E-feelings, mental action, and self-ascription of mental states based on epistemic rules. In the context of self-knowledge, these remarks suggest the existence of means of forming self-ascriptions other than the ascent routine.